Cross-linking of collagen fibrils leads to preferential gap zone mineralization in vitro - Ruixin Gao; Liza-Anastasia DiCecco; Liyang Zhong; Magdalena Wojtas; Karina Carneiro; Kathryn Grandfield; Eli D. Sone (Proceedings of the National Academy of Sciences, 2026)
Collagen mineralization is fundamental to the structure and mechanical properties of bone. Many in vitro models of collagen mineralization have been developed to understand the regulation, from the structure of collagen fibrils to the matrix noncollagenous proteins. However, most models using reconstituted collagen fibrils fail to reproduce preferential gap-zone mineralization, an important hallmark of natively mineralized collagen. This study focuses on the effect of chemical cross-linking on collagen mineralization, particularly the initial preferential mineral distribution in the gap zone. Mineralized cross-linked collagen fibrils show clear mineral preferential distribution and better alignment of the mineral (002) planes compared to un-cross-linked fibrils. Cross-linked collagen fibrils show enhanced stiffness and notably a larger difference in compressive modulus between gap and overlap zones, along with a reduced number of charged groups. Amino acid capping reactions were used to reduce the number of charged groups on collagen as a comparison to cross-linking without changing the stiffness. Amine/carboxyl-capped collagen fibrils show better crystal alignment but not preferential gap-zone mineralization. Together, these results lead to the surprising suggestions that stiffness of collagen fibrils plays an important role in the preferential gap zone deposition of mineral, while the charge of collagen affects the degree of mineral alignment.